Local Delivery of a Synthetic Endostatin Fragment for the Treatment of Experimental Gliomas - Pradilla, Gustavo (2005)
OBJECTIVE: Endostatin is an anti-angiogenic agent that blocks matrix-metalloproteinase-2 and inhibits endothelial cell proliferation. Currently, endostatin is available through recombinant technology, which limits its broader use. In this study, a synthetic endostatin fragment (EF) was analyzed to determine its anti-angiogenic properties when locally delivered by controlled-release polymers and to establish its effect as a treatment for experimental gliomas. METHODS: Cytotoxicity of EF against 9L gliosarcoma and F98 glioma was determined in vitro. EF was loaded into polyanhydride-poly-(bis-[carboxyphenoxy-propane]-sebacic-acid) (pCPP:SA) polymers at increasing concentrations. Pharmacokinetics of the EF/polymer formulations were defined in vitro. Anti-angiogenic properties of the EF/polymer formulations were evaluated in the rat-cornea micropocket assay. Toxicity and efficacy of locally delivered EF polymers either alone or combined with systemic bischloroethylnitrosourea (carmustine) were determined in rats intracranially challenged with 9L gliosarcoma. RESULTS: EF showed scarce cytotoxicity against 9L and F98 in vitro. EF/pCPP:SA formulations showed sustained release by day 19. Mean corneal angiogenesis index 20 days after tumor implantation was 4.5 ± 0.7 for corneas implanted with 40% EF/pCPP:SA compared with controls (8.5 ± 1.3, P = 0.02). Intracranial efficacy studies showed that EF polymers alone did not prolong animal survival. Combination of 40% EF/pCPP:SA polymers with systemic bischloroethylnitrosourea (carmustine) prolonged survival (median survival of 44 d, P = 0.001) and generated 33% long-term survivors. CONCLUSION: Controlled-release polymers can effectively deliver a biologically active EF in a sustained fashion. EF inhibits angiogenesis in vitro and in vivo, and even though EF does not prolong survival as a single agent, it exhibits a synergistic effect when combined with systemic bischloroethylnitrosourea (carmustine) in the intracranial 9L gliosarcoma model.